2001
DOI: 10.1007/3-540-45451-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Active Networking Support for the Grid

Abstract: Grid computing is a promising way to aggregate geographically distant machines and to allow them to work together to solve large problems. After studying Grid network requirements, we observe that the network must take part of the Grid computing session to provide intelligent adaptative transport of Grid data streams. By proposing new intelligent dynamic services, active network can be the perfect companion to easily and efficiently deploy and maintain Grid environments and applications. This paper presents th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The main idea is to reserve the resources and to run the jobs on top of them. Other advanced QoS concepts and architectures have been tested in experimental platforms: Equivalent Differentiated Services (EDS) [14], programmable networks [15], active networks [16], DiffServ-IntServ [17].…”
Section: G-qosm Supports Many Types Of Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main idea is to reserve the resources and to run the jobs on top of them. Other advanced QoS concepts and architectures have been tested in experimental platforms: Equivalent Differentiated Services (EDS) [14], programmable networks [15], active networks [16], DiffServ-IntServ [17].…”
Section: G-qosm Supports Many Types Of Resourcesmentioning
confidence: 99%
“…Most current Grid services are provided over best-effort (BE) networks. Thus, QoS architectures originally developed for IP such as DiffServ (DS) have been adapted to Grid environments: GARA [6], NRSE [7], G-QoSM [8], GNRB [9] and [10][11][12][13][14][15][16][17]. Nevertheless, none of those proposals has been widely adopted yet.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies have shown that Grid systems can benefit from active networks technologies [12,15,13], thus a novel networking paradigm called Active Grid has been proposed. The main idea is to place active network nodes (ANNs) at strategic points in the network and to make processing and caching capabilities of ANNs explicitly available to Grid applications.…”
Section: Introductionmentioning
confidence: 99%
“…The main idea is to place active network nodes (ANNs) at strategic points in the network and to make processing and caching capabilities of ANNs explicitly available to Grid applications. Examples of such Active Grid configurations include Meta-cluster computing, where an ANNs is used as a network head of each cluster or parallel computer, and Global computing, where an ANN is used to manage a single Grid node or a collection of Grid nodes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to traditional GRIDs, which are based on traditional IP networks, packet interception [34], [35] is inherently supported in programmable GRIDs, since ANNs embody the flexible store-compute-an-forward model, which is in contrast to the store-and-forward model of traditional IP routers. Thus, by definition, ANNs in programmable GRIDs can intercept packets destined for some other IP address, process them in a specific way (aside from routing), and then forward them towards their destination.…”
Section: Message Type (Mt 4 Bits)mentioning
confidence: 99%